Open Distance Learning: Bridging the Gap between Instructional Planning and Prescribed Standard: Sidra Rizwan, Rehana Masrur (PJDOL, 2023)
This research paper aimed to study the prevailing levels ofn instructional planning and strategies according to three criteria i) Comprehension, ii) Behavior iii) Performance possessed by the teachers in secondary schools, the relationship among the prevailing levels of the three criteria of instructional planning and strategies of teachers teaching at secondary level. It was a mixed methods research study.